2021
DOI: 10.1016/j.esmoop.2021.100102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell surface targets for CAR-T cell therapies and antibody–drug conjugates in breast cancer

Abstract: Background Two promising therapeutic strategies in oncology are chimeric antigen receptor-T cell (CAR-T) therapies and antibody–drug conjugates (ADCs). To be effective and safe, these immunotherapies require surface antigens to be sufficiently expressed in tumors and less or not expressed in normal tissues. To identify new targets for ADCs and CAR-T specifically targeting breast cancer (BC) molecular and pathology-based subtypes, we propose a novel in silico strategy bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…ITGB6, which is highly expressed in colorectal cancer, is associated with a poor prognosis ( 37 ). ITGB6 can also be used as a tumor-specific surface antigen (TSA) to identify cell surface targets of CAR-T cell therapy and antibody-drug conjugates in breast cancer ( 38 ). Studies have shown that ITGB6 was a liver-metastasis-related gene for PAAD patients ( 39 ) and the overexpression of ITGB6 was significantly associated with advanced AJCC stage and histologic grade, and worse prognosis in pancreatic cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…ITGB6, which is highly expressed in colorectal cancer, is associated with a poor prognosis ( 37 ). ITGB6 can also be used as a tumor-specific surface antigen (TSA) to identify cell surface targets of CAR-T cell therapy and antibody-drug conjugates in breast cancer ( 38 ). Studies have shown that ITGB6 was a liver-metastasis-related gene for PAAD patients ( 39 ) and the overexpression of ITGB6 was significantly associated with advanced AJCC stage and histologic grade, and worse prognosis in pancreatic cancer ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such antigens should have specific characteristics, making them suitable for targeting with ADCs: differential expression between tumor (high expression) and normal tissues (low/no expression), surface location, and internalization after ligand interaction 12 . To identify promising candidate antigens with these features, in silico strategies are being developed using RNA‐sequencing and protein‐expression data to predict the most suitable antigens for targeting 115,116 . These strategies could inform the design of ADCs in the future, allowing the development of antigen maps of cancers and the identification of histologies most likely to benefit from particular conjugates.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In addition to the targets discussed above, other targets have also been explored as potential antigens for CAR-T cell therapy. A in silico analysis compared gene expression patterns to identify potential targets for breast cancer immunotherapy, resulting in 36 potentially tumor-surface antigens being discovered, including integrin beta-6 (ITGB6), fibroblast growth factor receptor-4 (FGFR4), and ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) 168 . Only a few studies focused on those potential targets to clarify their therapeutic effects; therefore, more investigation is needed to estimate their potentiality.…”
Section: Potential Targets For Car-t Cell Therapy In Breast Cancermentioning
confidence: 99%